50 Teaching and learning approaches simple, easy and effective ways to engage learners and measure their progress - Mansell, Sharron; Gravells, Ann, editor (London, 2019)
This reader-friendly and accessible text introduces 50 teaching and learning approaches and explores how they work in practice by taking an honest look at the advantages and disadvantages of each one.
Keywords: Learning; Learning, Psychology of